Canine papilomatosis - Vieira, Larissa Caixeta; Poggiani, Sabrina dos Santos Costa (Pubvet, 2015)
Canine papillomatosis is characterized by benign neoformation caused by infection of epithelial cells by species-specific papillomavirus. Six clinical syndromes related to papillomatosis are described in dogs, which include canine oral papillomatosis, genital papillomatosis, multiple footpad papillomas, papillomas characterized by pigmented plaques and cutaneous papillomatosis which include inverted cutaneous papillomatosis. The disease transmission occurs by direct or indirect contact with secretions or blood from papillomas present in infected animals. Diagnosis is based on clinical findings and complementary tests. Spontaneous resolution usually occurs in most cases, what makes it difficult to evaluate therapeutical approach efficacy. In general, the disease prognosis is good.